Upaya Guru Al-Qur’an Hadits dalam Meningkatkan Minat Baca Al-Qur’an Terhadap Siswa di MTs. Al-Hikmah Klitih Plandaan Jombang - Khoirul Huda; Moh. Irfan; Da’il Falach Mubarok (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2025)
ABSTRACT This study aims to describe the efforts of Al-Qur'an and Hadith teachers to increase students' interest in reading the Quran at MTs Al-Hikmah Klitih, Plandaan, Jombang. This study is qualitative, employing a descriptive qualitative and phenomenological approach. Data collection techniques included observation, interviews, and documentation. Data analysis involved several steps: data reduction, data presentation, and conclusion drawing or verification. The results indicate that efforts made by Al-Qur'an and Hadith teachers at MTs Al-Hikmah Klitih to increase students' interest in reading the Quran include habituating reading the Quran, providing memory reinforcement and writing practice, discussions with students, and assigning students to read the Quran while understanding the rules of recitation (tajwid). Interest in learning the Quran is high among some students, as almost all students are enthusiastic about reading the Quran. However, the average student's ability is still low, especially in tajweed. This is due to the method used being less than appropriate and the learning process being less engaging. Keywords : Teachers, Reading Interest, Quran, Students.